Pelatihan Bahasa Inggris untuk perbankan kepada siswa-siswa SMKS Khatolik Kefamenanu - Delti Yulita; Hesni Neno; Erlinda Sonya Pale (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
With the development of an increasingly sophisticated and global industrial era, SMK graduates are required to have adequate skills and be able to compete in the world of work, one of which is English skills. To meet these demands, it's necessary to improve the English skills of SMK students. Therefore, this service activity aims to train students' skills in the world of work, especially in banking. SMKS Khatolik is a vocational school growing quite rapidly in Kefamenanu and has opened a Banking department. However, teachers and students need to have sufficient and practical knowledge of English in banking. Therefore, this training provides a solution to increase students' knowledge and skills in using English for banking so that these SMK graduates will have more selling points to compete in the banking world. The training activities were carried out in 5 steps. First, to provide an overview of the banking world; the second meeting continued with vocabulary material in the banking world, and the third meeting focused on customer and teller service material. Then in the fourth and fifth meetings, students are given exercises and practice business presentations and correspondence in English. The results of this activity showed an increase in banking class students' ability to read, speak and write English. Students also acquire a lot of vocabulary related to the banking world, which helps them better understand the transaction process at banks in English.